An artificial intelligence‐based smart health system for biological cognitive detection based on wireless telecommunication. (8th March 2022) - Babu, Manikam; Jesudas, Thangaraju
Abstract: The framework described in this work is a propelled explication to diagnosis of the health condition of the individuals who is affecting from arthritis disease. The innovation underlying this is the Internet of Things (IoT), a propelled system in the current trend to combine sensor data to the visualization platform for improved comprehension. In this work, we fabricated a thin film‐based bio‐sensor for detecting uric acid (UA) in the blood which is used to diagnose the arthritis disease. The fabricated sensor is integrated with node microcontroller unit (MCU) unit to store the uric acid content data where it is processed and recorded. The logged information can be forwarded by utilizing IoT technology using Thing Speak application programming interfaces (APIs) key and the information refreshed from the framework can be available in the cloud connector. The data for visualization can be obtained by API, validated with the private key, and accessed using Thing Speak APIs on multiple platforms such as mobile, tablet, and laptop connected to the internet. So, in summary, Thing Speak API Handler ensures the legitimacy of data retrieval from the cloud and visualization across several platforms.